Unsaturated dietary fat increases egg size - A mechanism - Moudgal, R P (The Indian Journal of Animal Sciences, 2012)
Unsaturated dietary fat (sunflower oil) improves egg weight, deserves further elucidation of the possible but still unknown mechanism. Two isocaloric and isonitrogenous dietary regimens with or without 9% sunflower oil were fed to WL layers. On laparotomy, the preovulatory follicles (Fâ‚) from both of the groups were similar in weight but the moisture in the yolk of ovarian follicle obtained from sunflower oil fed group was significantly (P